Ethiopia’s nationhood reconsidered - Levine, Donald N. (2011)
Conventional theories trace nationalism to modern Western Europe, usually following the French Revolution. However, markers of nationalism used by most scholars are attested by evidence of Ethiopia’s nationhood as early as sixth century C.E. This requires revisions in both conventional notions of nationhood and views of those who find Ethiopianness a recent invention. Moreover, the experience of Ethiopians in their recent Diaspora warrants rethinking the very notions of nationhood. Continuing ties of Ethiopian expatriates with their homeland and communication through electronic media manifest a new configuration of  Ethiopia’s nationhood, consisting now of three confluent parts: bet-agar (homeland); wutch-agar (diaspora); and sayberagar (cyberspace).